2003
DOI: 10.1590/s0103-50532003000300021
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from Terminalia glabrescens

Abstract: Das folhas de Terminalia glabrescens foram obtidos um novo triterpeno pentacíclico (3β,6β,23,28-tetraidroxiolean-12-eno), além dos ácidos ursólico, 2α-hidroxiursólico, oleanólico, maslínico, arjunólico, sumaresinólico e asiático, esqualeno, fitol, sitosterol-3-O-β-D-glucopiranosídeo e nalcanos. Da casca do caule foram obtidos friedelina, taraxerol, lupeol, lupenona, betulina, betulona, ácido betulínico, arjunglucosídeo I, estigmastano-3β,6α-diol, β-sitosterol, (-) catequina, β-Dpiranotagatose, β-D-furanofrutos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 12 publications
5
18
0
3
Order By: Relevance
“…Therefore, the structure of the isolated compound (Figure 1) was assigned based on the chemical shifts obtained from 1D, 2D ( 1 H and 13 C NMR) which revealed the presence of 30 carbons typical of friedelane skeleton. [18][19][20] To the best of our knowledge, this is the first report of the presence of friedelin in peels M. domestica. Compound 2 was identified as betulinic acid respectively, by comparison of their NMR, MS and physical data with those described in the literature.…”
Section: Structure Elucidationmentioning
confidence: 65%
“…Therefore, the structure of the isolated compound (Figure 1) was assigned based on the chemical shifts obtained from 1D, 2D ( 1 H and 13 C NMR) which revealed the presence of 30 carbons typical of friedelane skeleton. [18][19][20] To the best of our knowledge, this is the first report of the presence of friedelin in peels M. domestica. Compound 2 was identified as betulinic acid respectively, by comparison of their NMR, MS and physical data with those described in the literature.…”
Section: Structure Elucidationmentioning
confidence: 65%
“…A configuração β-axial para a segunda hidroxila, ligada a C-6, foi definida pelo sinal em δ 4,58 (1H, sl, W h/2 = 9 Hz), indicativo de hidrogênio α-equatorial e consistente com o relatado na literatura para triterpenóides 6β-substituídos 2,9,10 . A análise dos dados disponíveis para o triterpenóide 1 permitiu identificá-lo como o 3β,6β-diidroxi-olean-12-eno.…”
Section: Resultsunclassified
“…Os dois gêneros de maior ocorrência são Combretum e Terminalia, cada um com 250 espécies, sendo extensamente usadas na medicina tradicional da África 1 . As plantas do gênero Terminalia são amplamente distribuídas nas áreas tropicais do mundo e conhecidas como uma fonte rica de metabólitos secundários, tais como triterpenóides pentacíclicos e seus derivados glicosilados, flavonóides, taninos e outros compostos aromáticos 1,2 . As espécies do gênero Terminalia apresentam diversas atividades farmacológicas reveladas pelos extratos ou substâncias isoladas, tais como antifúngica, antimicrobiana, antioxidante, antidiabética, anti-HIV-1, antimalárica e outras 3 .…”
Section: Introductionunclassified
“…Phytochemical studies performed on different Terminalia species have demonstrated the occurrence of several classes of active constituents, such as tannins, pentacyclic triterpenes and their glycoside derivatives, flavonoids and other phenolic compounds [10].…”
Section: Phytochemical Studiesmentioning
confidence: 99%